The Liturgical Furnishings of the City Basilica at Patara in the Early Byzantine Period: Division of the Nave and the Monolithic Slabs - Demirton, Ceren (Istanbuler Mitteilungen, 2022)
This study investigates the slabs which were recovered from the excavations of the City Basilica at Patara in 2013–2019. Their motifs, dimensions and materials are described and compared with similar examples from Byzantine architecture, while their functions are determined and a possible re-construction is put forward. This typological study is the result of a scientific analysis of the slab construction methods and a structural examination of the basilica. A total of 190 liturgical limestone and marble artifact pieces which date back to the Early Christian Period have been found in the City Basilica at Patara. Since no such definition is forthcoming from Byzantine architectural studies, a new definition of these pieces as monolithic slabs has been proposed for those which are made of solid limestone with four-side trapezoidal cross-section, which are thought to have been used in the division of the nave. As a result of this study, it has been concluded that the slabs in monolithic form were used in the aisles on the northern and southern sides, and likely separated the naos of the basilica. The slabs in monolithic form which were found in the City Basilica at Patara are similar to others in Byzantine architecture in terms of their motifs, construction techniques and materials. They also originate from the architectural phase of the basilica, making it possible to date them to the second half of the 5th century A.D.